STRATEGI MENANAMKAN PEDULI SOSIAL ANAK USIA 5-6 TAHUN DI TK ISLAM AL-KAUTSAR PONTIANAK SELATAN - Aulia Mahfira; Marmawi R; Annisa Amalia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the strategy of instilling social care for children aged 5-6 years in AL-Kautsar Islamic Kindergarten, South Pontianak. The research method used is descriptive qualitative. The subjects of this study were the head of the kindergarten, the deputy head of the kindergarten, and teacher of group B at the AL-Kautsar Islamic Kindergarten, South Pontianak. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis was carried out, namely data collection, data reduction, data presentation, and drawing conclusions. Techniques for checking the validity of the data are triangulation. The results of this study indicate that: 1. Communication strategies are carried out to convey messages about social care so that they can be accepted by children. 2. The exemplary strategy is carried out to provide exampes of social care. 3. Habituation strategies are used to familiarize children with sosial care. 4. Storytelling strategies are used to convey stories that contain values about social care. The conclusion in this study is a method that is deliberately prepared by the teacher in instilling the character of social care in childen aged 5-6 years.